The valorization of waste ice cream into alcohol - Amanda L. Miller; John A. Renye, Jr.; David B. Johnston; Jennifer Thomas; Adam M. Oest; Rafael A. Garcia; Peggy M. Tomasula (Journal of Dairy Science)
ABSTRACT: Valorization of food waste or food byproducts into higher-value products can benefit the food industry by contributing to the food supply chain. This study aimed to investigate the potential for using waste ice cream as a fermentation substrate for production of ethanol by yeast. Results showed that 2 Saccharomyces cerevisiae strains, Lalvin EC-1118 (Lallemand Inc.) and Ethanol Red (Lesaffre), were able to ferment an aqueous byproduct of waste ice cream, resulting in the production of ethanol, ∼7% (wt/vol). This most likely occurred due to the utilization of free monosaccharides or sucrose, because they were unable to ferment lactose. Lactase and glucoamylase were added, to increase the availability of fermentable carbohydrates, resulting in 9.77% and 9.30% (wt/vol) ethanol produced by Lalvin EC-118 and Ethanol Red strains, respectively. Both strains were also shown to not utilize the galactose released following the hydrolysis of lactose. Maximum ethanol production, above 13% (wt/vol), was seen in samples treated with a combination of lactase and a protease, suggesting that a lack of nitrogen was stalling the fermentation. A benchtop-scale distillation was performed using a fermented vanilla ice cream treated with protease, lactase, and diammonium phosphate. The distillation was successful, and several fractions with various aromas and odors were collected. Results from this study suggest that that ethanol production is a viable valorization strategy to produce distilled beverage alcohol from waste ice cream, which is expected to be free of protein allergens.